Atlas of Polymer Structures - Morphology, Deformation and Fracture Structures - Michler, Goerg H. (Hanser Publishers, 2016)
Structure and morphology determine the properties of polymeric materials. This atlas provides, with well over 2000 high-quality micrographs, a comprehensive overview of the structural/morphological diversity of all classes of polymers. All microscopic techniques from light microscopy through scanning and transmission electron microscopy to atomic force microscopy are covered. Another focus is on the changes in polymer morphology occurring under mechanical stress, i.e. the deformation and fracture structures. The extensive visual material will help professionals in research and application fields to determine structure-property correlations of polymeric materials and also improve training and teaching in universities. The organized structure of the book based on polymer groups - together with helpful tables to guide the reader easily to the appropriate images according to polymer type, morphological detail, deformation structure, or other structural detail - make this a user-friendly reference for all interested in structure and properties of polymeric materials.